PENINGKATAN KAPASITAS DESA ANJANI DALAM MENGHADAPI BENCANA KEBAKARAN - Farizky, Rijal Muhammad; Daffa, Mohammad Abiyyu; Mahmuda, Sabina Ngestiara; Azim, Arsil; Ramadhania, Dinda; Aprianti, Egi; Nurita, Metri; Syahramdani, M. Satya; Rivan, Muhammad Faizur; Marthaleza, Siska (Universitas Mataram, 2024)
Kuliah Kerja Nyata (KKN) Program represents the commitment of higher education institutions to engage with the community, involving active participation of students and lecturers in various field activities. One of the main focuses of the KKN at Universitas Mataram in 2023 is the development of Disaster-Resilient Villages aimed at enhancing the readiness and self-reliant response of village communities to potential disaster threats. Desa Anjani, as an area that has experienced several fire incidents in the last two years, faces significant challenges regarding the awareness and understanding of the community about safe and responsible environmental management practices. The development of Disaster-Resilient Villages through KKN activities aims to increase the capacity of Desa Anjani in dealing with fire disasters and to conduct mapping of fire-prone areas in Desa Anjani. Capacity building is carried out through outreach activities and practical application. Mapping is conducted to identify fire-prone areas and map out infrastructure and resources that can be used for mitigation and disaster management purposes.